Canadian Library Human Resources Short-Term Supply and Demand Crisis Is Averted, But a Significant Long-Term Crisis Must Be Addressed - McKenna, Julie (Evidence Based Library and Information Practice, 2007)
Objective – To examine the human resources environment in Canadian libraries in order to assess readiness to accommodate change and to identify opportunities for human resources planning. The “8Rs” of the study were defined as recruitment, retirement, retention, remuneration, repatriation, rejuvenation, re-accreditation, and restructuring. Design – This study was undertaken in three phases over nearly three years through the use a variety of methods including literature review, analyses of existing data (Statistics Canada and library school graduate data), telephone interviews (with senior library administrators), focus groups (with representatives from Canadian Association of Research Libraries, Canadian Urban Libraries Council and Alberta Association of Library Technicians), print surveys (library institutions) and web-based surveys (of professional librarians and paraprofessional library staff). Setting – Canadian libraries that are not component branches of a system, and that employ professional librarians. Subjects – Stage I: 17 senior library administrators participated in telephone interviews and three focus groups were conducted.Stage II: Surveyed library administrators representing institutions. A multi-stage stratified random sampling technique was used to ensure geographical representation from each of Canada’s provinces and territories. Full census participation was conducted for members of the Canadian Association of Research Libraries and the Canadian Urban Libraries Council. The print survey instrument was distributed to 1,357 subjects; 461 completed surveys were returned (response rate of 34% with results for the total sample accurate within plus or minus 3.8 per centage points, 95 times out of 100).Stage III: Surveyed professional librarians and paraprofessional staff. Multi-stage random sampling was used to ensure representation of library staff from all library sectors and sufficient sub-sample sizes. Of the 12,472 individuals in the sampling frame, 8,626 were notified of their selection to participate in the web-based survey. Corrections were made to e-mail addresses and 7,569 e-mail invitations with the survey URL were sent successfully. Of the 8,626 potential respondents, 3,148 librarians and paraprofessionals participated (for a response rate of 37%). A non-random Canada-wide call for participation was distributed to library staff who had not been represented in the sampling frame via the listservs of 56 library associations. This provided an additional 1,545 respondents and the total sample size increased to 4,693 for a confidence interval of plus or minus 1.2%, 95 times out of 100. The non-random data from the Canada-wide call was kept in a separate dataset file. Methods – Stage I began with a literature review and analysis of existing Statistics Canada and library school graduate data. Three focus group sessions with representatives from Canadian Association of Research Libraries, Canadian Urban Libraries Council and Alberta Association of Library Technicians were held and in-depth telephone interviews were conducted in May 2003 with 17 senior library administrators. Transcripts were thematically coded and summarised. The interview guide is available as Appendix E of the report. The results of Stage I were used to inform the design of the two survey instruments (Stages II and III). Stage II was a 17-page print survey informed by insights gathered in Stage I and was sent to library directors in the summer of 2003. The print mail-out of the institutional survey was sent to libraries that employed at least one librarian and were not a component branch of another system. A copy of the institutional survey is available as Appendix C of the report.Stage III was a web-based survey of librarians and paraprofessional library staff undertaken in the summer of 2004 using random and non-random sampling methods. This survey was developed from insights gathered in Stages I and II. A copy of the individual survey is available as Appendix D of the report. Main results – The analytical focus of the 275-page report is on the broad Canadian library sector. Data and analysis are provided by type of library, type of staff, and by geographical regions where sufficient response rates have allowed reporting. Although the role of the paraprofessional is examined in many sections of the report, the principal focus is on the professional librarian.Nine sections of the report present results, analysis and strategic human resource planning implications. Highlights for the broad Canadian library environment are briefly described below. Each section of the report provides further breakdown by library sector, type of position, career stage and other variables that provide significant insight.Workplace Demographic Characteristics (Section C)This section provides demographic information about those in supervisory or management roles (62% of librarians), union density (67% of librarians and 79% of paraprofessional staff), longevity in career, part-time employment, and gender, along with other characteristics. Results conclude that visible minorities and Aboriginal staff are under-represented across all types of libraries and that few libraries recognise the credentials of immigrant librarians.Recruitment to the Profession and to the Organization (Section D)Positive exposure to libraries and librarians is the best predictor of librarianship as a career choice and there were no significant differences in the original motivations for choosing the professional librarian career between new professionals and senior librarians. In response to the open-ended question about motivation for choosing librarianship, none of the librarian respondents (n=1,823) indicated leadership, managing libraries or supervising others as their reason (p. 52). Many respondents indicated reasons for choosing the profession that are in alignment with the values of librarianship, but few indicated reasons that reflect the real nature of the librarians’ role. The average age of new librarian recruits is 37 (with little variation between sectors).Thirty per cent of paraprofessionals are interested in pursuing an MLIS degree; 29 per cent are not interested because they are satisfied with their current role. The major barriers for paraprofessionals wishing to pursue the MLIS degree are inadequate or unrecognised credentials (21% - although 45% of paraprofessionals have an undergraduate degree), geographic distance (33%), lack of money (48%), and lack of time (49%).Eighty per cent of libraries report that the major barrier to recruiting is budget constraints; other barriers include small size of library (60%), organizational hiring freeze (54%), inadequate librarian pay (54%), geographic location (52%), inadequate pool of qualified candidates (51%), and inadequate pool of interested candidates (50%).The ten most important and difficult-to-fill competencies when recruiting varied significantly for each sector: leadership potential, ability to respond flexibly to change, and ability to handle high-volume workload were the three highest-ranked competencies across all libraries.Retirement (Section E)Canadian libraries experienced librarian retirements (11% of total current workforce) and paraprofessional retirements (7% of total current workforce) between 1997 and 2002. During this period, 79 per cent of librarians retired before age 65. Forty per cent of librarians over age 50 estimate that they will retire between 55 and 60. Only 9 per cent of libraries have a succession plan.Staff Retention: Inter- and Intra-organizational Mobility (Section F)Librarians are satisfied with their work and stay in their organization because they like the job (85%), co-workers (84%), and workplace (79%). Seventy-seven per cent of senior librarians and 87% of senior paraprofessionals have been at their current library for more than 10 years. Sixty-nine per cent of librarians believe they are qualified to move to higher level positions, but 69% of institutions state that limited librarian turnover contributes to a lack of promotional opportunities.Education (Section G)Seventy-five per cent library administrators agree that MLIS programs equip graduates with needed competencies, but 58% recommended that the programs provide more management, business and leadership training. Seventy-six per cent of administrators believe that they have little or no input into curriculum content of MLIS programs.Overall evaluation of MLIS education by recent librarian entrants is not positive. Only forty-four per cent indicated that the program provided a realistic depiction of the job, while only 36% said the program provided a realistic expectation of work in their library sector. Recent librarian entrants (67%) were satisfied with the overall quality of their MLIS program, but few indicated that their program provided them with the necessary management skills (25%), leadership skills (20%), or business skills (12%) for their position. Recent library technician entrants were more satisfied (81%) with their programs’ success in providing general skills (87%), and providing a realistic depiction of the job (72%).Continuing Education (Section H)New librarians (72%) need a significant amount of ongoing training, but only 56% believe that their institution provides sufficient training opportunities. Only 30% of libraries have a routine method for determining training needs of librarians and fewer (13 %) have an evaluation method for training outcomes. In most cases, about half of those who received training reported that it improved their job performance.Quality of Work and Job Satisfaction (Section I)Librarians and paraprofessionals are satisfied with their jobs (79% for each) and librarians (72%) and paraprofessionals (61%) agree that their salary is fair. Most libraries offer a wide range of benefits to their employees, including life insurance (95%), pension plan (92%), and medical benefits (88%). Librarians (80%) and paraprofessionals (70%) are satisfied with their benefits.Although a low percentage of librarians agreed that they have little job stress (24%) and only 39% found their workload to be manageable, 62% of librarians agree that their work allows work, family and personal life balance. The statistics are slightly more positive for paraprofessionals.There is a gap between the desire to be treated with respect (98% for all workers) and the perception that respect is conveyed (77% of librarians and 75% of paraprofessionals). A similar gap exists between desire to be involved in decision-making and actual involvement. The two most important factors for job satisfaction for all library workers are respectful treatment and a job that allows them to learn new skills and grow.Numerical Librarian Demand-Supply Match (Section J)Libraries hired more librarians than they lost in 2002, for a net three per cent increase. Many library administrators believe that there will be a five-year increased demand for librarians (77%) and paraprofessionals (81%).The short-term supply (next 5 years) of new librarians to replace departures due to retirements is predicted to have the capacity to fill 98 per cent of the current librarian positions; the capacity to replace library technicians is 99 per cent. The long-term supply (next 10 years) of new librarians to replace departures due to retirements is predicted to have the capacity to fill 89 per cent of the current librarian positions; the capacity to fill technician positions is identical. These predictions are based on no growth in the number of positions in the future.Match Between Organizational Job Function Demand and Individual Staff Supply of Skills, Abilities, Talents, Interests (Section K)Libraries report that increased use of information technologies (87%) and re-engineering (61%) have contributed the greatest change in the roles of librarians. Libraries report that more librarians have been required to perform a wider variety of tasks in the past five years (93%) and that this trend will continue over the coming five years (94%).A high percentage of libraries (86%) reported that over the past five years librarians have been expected to perform more management functions and 56% of mid-career and senior librarians believed this had occurred. Libraries (88%) believe that this trend will continue; only 44% of librarians indicate interest in performing management functions.Mid-career and senior librarians report that job stress has increased over five years ago. Requirements to work harder (55%), perform more difficult tasks (56%), perform a wider variety of tasks (69%), and perform more managerial functions (56%) are the contributing factors. The performance of a wider variety of tasks and more difficult tasks was significantly related to the assessment by librarians that their jobs were more enjoyable, interesting, rewarding and challenging.Institutions (78%) reported the increased need for paraprofessionals to perform librarian tasks over the past five years and believe that this will continue (77%). Only 28% of paraprofessionals believe they are currently required to perform more librarian tasks. Conclusion – The need to confirm the existence and magnitude of the crisis that will be created by upcoming retirements in Canadian libraries was a primary motivator for this study. Conclusive results were obtained that should inform each sector and geographic area in Canada. The percentages of staff over the age of 55 (librarians: 25%; paraprofessionals: 21%) is much greater than that of the Canadian workforce (11%). If there is no growth in the number of positions needed, there will be no short-term supply-demand crisis to fill the gaps left by retirements. There will be a librarian and technician shortage in ten years (a shortfall of 11% of the current supply) and a more significant crisis if the predicted growth in staffing is factored in. Recruitment to the librarian and technician professions is critical and the paraprofessional staff may be a potential pool of future MLIS candidates if the accessibility issues associated with the programs are addressed. Only nine per cent of organizations have a succession plan in place. There is great opportunity for the development of strategic solutions.In response to the open-ended question about motivation for choosing librarianship, no respondent indicated leadership, managing libraries or supervising others as their reason. This is of concern when 62% of librarians today work in a managerial role. Management and leadership skills are a significant concern for recent graduates, administrators, and librarians, with all indicating that the workplace needs are greater than the current preparedness. More cooperation with MLIS programs and professional associations is essential to ensure that leadership and management skill development are supported through the curricula and continuing education planning. Organizations must also develop and support a culture where leadership is encouraged and expected, and recognised.There is a need for further development of continuing education opportunities, and training needs assessment and outcome assessment programs may be beneficial. Paraprofessionals and new librarians are less satisfied with the workplace training opportunities available to them than librarians in later stages of their careers.Role change will continue in libraries and planning will be essential to ensure that restructuring reflects the competencies that will be needed in the new mix. Workload and job stress appear to be rising and will require careful monitoring. There may be opportunity to define roles for “other” professionals in libraries.Library staff have a tendency to stay in their institution for much of their career, making decisions in the recruitment and hiring processes of critical importance. Loss of employees due to turnover is not a problem for most libraries, but the lack of turnover has affected the promotional opportunities for those who desire upward mobility.An interesting recommendation was made that two or more libraries may realise both cost savings and benefits through the sharing of staffing resources. If issues surrounding credentials can be addressed, there may be a potential pool of future immigrant librarians.